Folded Synthetic Peptides and Other Molecules Targeting Outer Membrane Protein Complexes in Gram-Negative Bacteria - Robinson, John A. (Frontiers in Chemistry, 2019)
Conformationally constrained peptidomimetics have been developed to mimic interfacial epitopes and target a wide selection of protein-protein interactions. ß-Hairpin mimetics based on constrained macrocyclic peptides have provided access to excellent structural mimics of ß-hairpin epitopes and found applications as interaction inhibitors in many areas of biology and medicinal chemistry. Recently, ß-hairpin peptidomimetics and naturally occurring ß-hairpin-shaped peptides have also been discovered with potent antimicrobial activity and novel mechanisms of action, targeting essential outer membrane protein (OMP) complexes in Gram-negative bacteria. This includes the Lpt complex, required for transporting LPS to the cell surface during OM biogenesis and the BAM complex that folds OMPs and inserts them into the OM bilayer. The Lpt complex is a macromolecular superstructure comprising seven different proteins (LptA-LptG) that spans the entire bacterial cell envelope, whereas the BAM complex is a folding machine comprising a ß-barrel OMP (BamA) and four different lipoproteins (BamB-BamE). Folded synthetic and natural ß-hairpin-shaped peptides appear well suited for interacting with proteins within the Lpt and BAM complexes that are rich in ß-structure. Recent progress in identifying antibiotics targeting these complexes are reviewed here. Already a clinical candidate has been developed (murepavadin) that targets LptD, with potent antimicrobial activity specifically against pseudmonads. The ability of folded synthetic ß-hairpin epitope mimetics to interact with ß-barrel and ß-jellyroll domains in the Lpt and Bam complexes represent new avenues for antibiotic discovery, which may lead to the development of much needed new antimicrobials to combat the rise of drug-resistant pathogenic Gram-negative bacteria.